2m-3=m

Simple and best practice solution for 2m-3=m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2m-3=m equation:


Simplifying
2m + -3 = m

Reorder the terms:
-3 + 2m = m

Solving
-3 + 2m = m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
-3 + 2m + -1m = m + -1m

Combine like terms: 2m + -1m = 1m
-3 + 1m = m + -1m

Combine like terms: m + -1m = 0
-3 + 1m = 0

Add '3' to each side of the equation.
-3 + 3 + 1m = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 1m = 0 + 3
1m = 0 + 3

Combine like terms: 0 + 3 = 3
1m = 3

Divide each side by '1'.
m = 3

Simplifying
m = 3

 

You can always share this solution

See similar equations:

| 4x+30=3x+110 | | 2x^2+3xy-2y^2=0 | | -9i-17=-26 | | 6x+3+1-9=3x+4x | | -6y+12y-3y= | | 7x-y+9-19x-4y+5= | | 2x-4.6=6.2 | | -x=5(-6-7x) | | 4x-13+4y+7-9y+16x=0 | | -2.06d+18=-10.84 | | 306=-8(3+6n)-7n | | 19=k+7+2k | | 8x^2+68x=36 | | 4m-12= | | 5a-6b-11a+13b= | | 68.1m=cm | | 8(4x+3)=4x+1-2x | | 7(v-7)=-84 | | x+3.5=6 | | 6+6x=-54 | | 9u-3=19 | | 6x+13y=7 | | -1.8+2.4a=6.6 | | -3x-10=-40 | | -6-2b=4b+3b | | 3z+4z+4=1 | | 8m-3=19 | | -2(2-2x)-4(x+5)=-24 | | 3y-4=14 | | 9x-4=6x+11 | | 2x+10=26 | | -84=7(v-7) | | 36=j-11 | | 28=d-42 | | -2(5+6n)=6(8-2n) | | 8x-12=36 | | 17=r-2 | | 7x+4=67 | | 2x^2-9x=-6 | | 2x^2-9x^2=-6 | | 35x^2-23x-4=0 | | x+8=-15 | | 9+2n=2-3n | | -6(1+7k)+7(1+6k)=-2 | | 2x^2-9x=6 | | -7-4x=-27 | | 10+2k=8k+4 | | -(7p+9)+(3p-1)= | | 8=2n-4 | | -8(7-8x)-2=-122 | | 7x^2+13x-2=0 | | 20=2y | | 12+9z=8+-4z | | 13=6+7c | | e+2= | | 5+2r=23 | | 2k=4 | | -1-7x=-43 | | z+4.1=9.6 | | nd=1.08t | | c-2.4=1.8 | | 4h-10=6 | | 7t-(6t-2)= | | -2m-3*-3m-2=m | | -6+7x-6x=3 |

Equations solver categories